2016
DOI: 10.1002/hpm.2340
|View full text |Cite
|
Sign up to set email alerts
|

The effect of health transformation policies on the resident physicians' perception of the medical profession in Turkey

Abstract: Although the new changes in the health system in Turkey has resulted in positive implications with respect to the groups that use the healthcare services, it has been singled out for criticism by the professional associations because of its erosive consequences particularly for the medical profession as a whole. The purpose of this study is to explain how the health transformation policies and practices influenced the working conditions and perceptions of the resident physicians in Turkey with regard to the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…Several studies and reports from Turkey have revealed similar ndings (3,35,39,57). For example, Erdem and Atalay found that residents perceive that the time they can spare for social activities, friends and family members has been restricted severely due to excessive workload because of health transformation policies in Turkey (39). As known, the medical profession permeates all layers of one's life, and the values intrinsic to the medicine practice are combined with the person's moral stance.…”
Section: Underlying Contextual Factors and The Prevalence Of Physicia...supporting
confidence: 68%
See 2 more Smart Citations
“…Several studies and reports from Turkey have revealed similar ndings (3,35,39,57). For example, Erdem and Atalay found that residents perceive that the time they can spare for social activities, friends and family members has been restricted severely due to excessive workload because of health transformation policies in Turkey (39). As known, the medical profession permeates all layers of one's life, and the values intrinsic to the medicine practice are combined with the person's moral stance.…”
Section: Underlying Contextual Factors and The Prevalence Of Physicia...supporting
confidence: 68%
“…The ndings suggest that the physicians think that the effect of P4P is not limited to their professional life, but also spreads to their private and social lives. Several studies and reports from Turkey have revealed similar ndings (3,35,39,57). For example, Erdem and Atalay found that residents perceive that the time they can spare for social activities, friends and family members has been restricted severely due to excessive workload because of health transformation policies in Turkey (39).…”
Section: Underlying Contextual Factors and The Prevalence Of Physicia...mentioning
confidence: 78%
See 1 more Smart Citation
“…While the impact of the health care reform in Turkey on the working conditions of physicians has been subjected to extensive research, 30 , 38 , 39 , 40 , 41 the research on the physician perceptions of the current health care system in Turkey is limited. 39 , 41 Moreover, there is a gap in the literature on physician perceptions about the hospital reimbursement models in Turkey – an issue which has been subjected to research in different countries. 22 , 24 , 25 , 42 Thus, this study aims to contribute to the literature on physician perceptions of the health care reform in Turkey by focussing on the DRG as a policy that shapes the medical practice of physicians.…”
Section: Turkey's Healthcare Reform and Hospital Reimbursement Regula...mentioning
confidence: 99%
“…introduced with the SDP were deprived of job security, the working conditions became more difficult (37), and the work peace was deteriorated due to the different wages (despite doing the same job) paid to the employees (38). It is emphasized that the new practice negatively affects working conditions such as increasing the workload of employees, insufficient education and personal development, and worsening economic and social conditions (39).…”
Section: And Latermentioning
confidence: 99%